Factors affecting students participation in extra-curricular - Mohamad Sari, N.; Esa, Ahmad (Elixir International Journal, 2017)
Extracurricular activity is a complementary of the requirement and interest in the student academic development. Extracurricular learning styles can be implemented in the form of informal where it can provide effective learning experiences to the students. In extracurricular development, every activity has its own goals and interests that can influence the students to participate in the particular activities. Nowadays, students are more likely to engage or spending their time with unbeneficial activities or isolate themselves in the virtual world. Several studies have been conducted and found that there are factors influence or prevent the students from participating in the extracurricular activities they intended to. These factors have been categorical into three main constraints; structural constraints, intrapersonal constraints, and interpersonal constraints. These main constraints referred to many factors that can influence student participation in extracurricular activities.